Patient experiences with depression care in general practice: a qualitative questionnaire study - Ina Grung; Norman Anderssen; Inger Haukenes; Sabine Ruths; Tone Smith-Sivertsen; Øystein Hetlevik; Stefan Hjørleifsson (Scandinavian Journal of Primary Health Care, 2022)
AbstractObjective To investigate patient experiences and preferences regarding depression care in general practice.Design and setting A qualitative study based on free-text responses in a web-based survey in 2017. Participants were recruited by open invitation on the web page of a Norwegian patient organization for mental health. The survey consisted of four open-ended questions concerning depression care provided by general practitioners (GPs), including positive and negative experiences, and suggestions for improvement. The responses were analysed by Template Analysis.Subjects 250 persons completed the web-based survey, 86% were women.Results The analysis revealed five themes: The informants appreciated help from their GP; they wanted to be met by the GP with a listening, accepting, understanding and respectful attitude; they wanted to be involved in decisions regarding their treatment, including antidepressants which they thought should not be prescribed without follow-up; when referred to secondary mental care they found it wrong to have to find and contact a caregiver themselves; and they thought sickness certification should be individualised to be helpful.Conclusions Patients in Norway appreciate the depression care they receive from their GP. It is important for patients to be involved in decision-making regarding their treatment.KEY POINTSDepression is common, and GPs are often patients’ first point of contact when they seek help.  • Patients who feel depressed appreciate help from their GP.  • Patients prefer an empathetic GP who listens attentively and acknowledges their problems.  • Individualised follow-up is essential when prescribing antidepressants, making a referral, or issuing a sickness absence certificate.